Mobile Rice Husk Gasifier Performance and Techno-Economic Analysis as Micro Scale Power Generation: Modeling and Experiment - Sarah Pertiwi; Yohanes Bobby; Marcellino Lorenzo; Hafif Dafiqurrohman; Adi Surjosatyo (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
Indonesia annually produces significant amounts of biomass waste in the agriculture sector. Rice husk, one of the highest produced agricultural waste materials, has sufficient caloric value to produce syngas in a gasification system to generate sustainable energy. However, the production of tar from rice husk gasification is significantly high, damaging the equipment and internal combustion engine. This study carried out performance analysis on a small-scale rice husk gasifier. A simulation provided a syngas composition overview and showed a maximum LHV value of 6.47 MJ/Nm3 at ER 0.25, and a maximum CGE value of 83% at a temperature of 900 ℃. Furthermore, the economic aspect of integrating renewable technology was also considered. The gasifier had an LCOE value ranging from 0.014 to 0.089 USD/kW, depending on the use of the gasifier. The feasibility of using a mobile rice husk gasifier was also inspected, based on net present value, benefit-to-cost ratio, and payback period.